Soil Carbon and Phosphorus after 40 Years of Contrasting Tillage and Straw Management in Dryland Wheat Production under Semi-Arid Temperate Climate - Sosibo, Nondumiso Zanele; Muchaonyerwa, Pardon; Dube, Ernest; Tsilo, Toi John (Land (Basel), 2022)
The effects of conservation strategies on soil organic carbon (SOC) and phosphorus (P) dynamics in dryland wheat under semi-arid temperate conditions are not well understood. This study quantified the effects of tillage and straw management on SOC concentrations and stocks and P fractions after 40 years of dryland wheat under a semi-arid temperate climate. The treatments were straw management (burned and not burned) combined with tillage methods (conventional tillage (CT), stubble mulch (SM), and no-tillage (NT)). Fertilizer nitrogen (N) and P were applied annually at 60 and 12.5 kg ha−1, respectively. The soils were sampled from 0–50, 50–200, 200–400, 400–600, 600–800, and 800–1000 mm depths, and analyzed using standard methods. The concentration of SOC was not affected by tillage and straw management, except in 200–400 mm where it was higher where the straw was burned rather than retained. The total C stock (0–1000 mm) was higher under NT with straw burning, CT with no burning, and SM, than NT with straw retention and CT with burning. In the topsoil, NT had significantly (p < 0.05) higher Bray 1 P, NaOH II Pi, and residual P than SM and CT, while burning straw increased Bray 1 P and NaHCO3 Pi concentrations. The findings imply that while the SOC concentration is not significantly affected by tillage, but is increased by burning in the subsoil only, the total C stock is improved by NT with burned straw, CT with straw retention, and SM, while the labile P fractions are increased by NT with burned straw, relative to CT with burned straw, in the semi-arid dryland wheat region.